2017
DOI: 10.1051/matecconf/201711601008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated temperatures on the properties of nanomodified rapid hardening concretes

Abstract: Abstract. Effects of elevated temperature exposure and hardening age on mechanical properties of nanomodified concrete are presented. The mass loss, compressive strength and shrinkage of the exposed to the elevated temperatures and cooled specimens were determined. Nanomodification by ultrafine mineral additives and polycarboxylate eter superplasticizer provides direct early structure formation, higher strength at early and later ages, and improved thermal resistance in a range of 200-350 °C of cementbase mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Much attention has especially been paid to the incorporation of silica (SiO 2 ) nanoparticles, with some commercial products already available on the market. It has been reported that nanosilica (NS) have a significant impact on accelerating the hydration process of cement (Singh et al 2011;Land and Stephan 2012;Skoczylas and Rucińska 2018a), refining the pore structure of cement matrices (Sikora et al 2016), improving early and long-term mechanical properties (Skoczylas and Rucińska 2018b), as well as improving the durability performance Submitted to special issue NANO-2018 within the 6th International Conference "Nanotechnologies and Nanomaterials" NANO-2018. of cementitious composites (Du et al 2014;Heikal et al 2016;Marushchak et al 2017). The beneficial effect of silica nanoparticles is attributable to three synergistic effects: (i) the filler effect-nanosized silica particles fill the voids in the cement matrix, decreasing paste porosity and optimizing the distribution of the pore structure; (ii) the nucleation effect-ultrafine silica nanoparticles act as the nucleation sites (kernels) for the hydration reaction of the cement; (iii) the pozzolanic effect-through the reaction of silica nanoparticles with calcium hydroxide (CH), the amount of calcium silicate hydrate (C-S-H) gel increases (Singh et al 2011(Singh et al , 2013Abd El-Aleem and Ragab 2014;El-Didamony et al 2016;Маrushchak et al 2016;Xu et al 2016;Rupasinghe et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has especially been paid to the incorporation of silica (SiO 2 ) nanoparticles, with some commercial products already available on the market. It has been reported that nanosilica (NS) have a significant impact on accelerating the hydration process of cement (Singh et al 2011;Land and Stephan 2012;Skoczylas and Rucińska 2018a), refining the pore structure of cement matrices (Sikora et al 2016), improving early and long-term mechanical properties (Skoczylas and Rucińska 2018b), as well as improving the durability performance Submitted to special issue NANO-2018 within the 6th International Conference "Nanotechnologies and Nanomaterials" NANO-2018. of cementitious composites (Du et al 2014;Heikal et al 2016;Marushchak et al 2017). The beneficial effect of silica nanoparticles is attributable to three synergistic effects: (i) the filler effect-nanosized silica particles fill the voids in the cement matrix, decreasing paste porosity and optimizing the distribution of the pore structure; (ii) the nucleation effect-ultrafine silica nanoparticles act as the nucleation sites (kernels) for the hydration reaction of the cement; (iii) the pozzolanic effect-through the reaction of silica nanoparticles with calcium hydroxide (CH), the amount of calcium silicate hydrate (C-S-H) gel increases (Singh et al 2011(Singh et al , 2013Abd El-Aleem and Ragab 2014;El-Didamony et al 2016;Маrushchak et al 2016;Xu et al 2016;Rupasinghe et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is widely used as a material for high-rise buildings, tunnels, drilling platforms, as well as nuclear facilities (having both satisfactory thermal and shielding properties) [ 5 , 6 , 7 , 8 ]. However, recent accidents involving existing structures have revealed that there is still a strong need to continue studies, in order to understand the effects of high temperature on cement-based materials, as well as to find methods for improving their thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of such accelerators in comparison with traditional ones is that the growth of early strength occurs without a decrease in the final strength. However, it is impossible not to notice the practical data of works [9,11,12], the authors of which also describe the significance of the effect of nanosized additives using the nanotechnological bottom-up approach on the acceleration of the processes of early structure formation of concrete. However, as a result of agglomeration processes, the effectiveness of such nanomodifiers as accelerators of hardening of cement systems may decrease.…”
Section: Discussion Of the Results Of The Study Of Ultra-high Strength Cementitious Compositesmentioning
confidence: 99%
“…At the same time, a combination of nanoadditives and superplasticizers presents significant prospects for improving the properties of cementitious composites. Thus, complex nanomodification of polycarboxylate superplasticizer and ultradispersed additives, as well as dispersed reinforcement with heat-resistant basalt fibers provides improved properties of concretes based on Portland cement, which were exposed to elevated temperatures of 200, 400 and 600 °C [12]. Such dispersion-reinforced composites based on cement systems are characterized by high early and standard strength due to optimization of particle packing with an increase in the density of the cement paste.…”
Section: And 1041 Mpa) It Has Been Established That the Complex Combination Of Portland Cement With Superzeolite Corundum Aggregate Basalmentioning
confidence: 99%